LINKING FOOD SYSTEMS TO HUMAN NUTRITION NEEDS: THE NUTRITION TRANSITION IN THE UNITED ARAB EMIRATES - Kubena, K. S. (Emirates Journal of Food and Agriculture, 2017)
Early recommendations for dietary intake of nutrients in humans focused upon nutritional deficiencies and their prevention. More recent recommendations were based on research that demonstrated relationships between nutrients and other dietary components and chronic disease. The study of genomics eventually will allow delineation of particular genes that are related to the development of disease and that vary in their responsiveness to intake of dietary components. The wealth of information on the role of dietary intake in optimal health from the whole organism to submolecular levels should promote optimal nutrition in newly developed countries in which food supply is adequate for all people, that is the nutrition transition has occurred there. However, inappropriate nutrition and the chronic diseases that are at least in part its result are increasing at epidemic proportions in many areas in the world. Obesity and type 2 diabetes mellitus are considered to be the result of lifestyle changes that include excessive energy intake and physical inactivity. Control of diabetes and hypertension can be prevented or improved significantly by modification of dietary intake and exercise. Data are accumulating about the involvement of nutrients and other dietary components in the development and treatment of cancer at various sites. Dietary intake affects maintenance of health and avoidance of disease across the life cycle. Efforts should be directed toward promoting a food supply that contributes adequate amounts of nutrients and other dietary components, such as phytochemicals and fiber, which are helpful in maintaining optimal health and in delaying or preventing chronic disease. Biotechnology can be used to improve crop yield and to enhance nutritional value and content of substances, such as phytochemicals, in foods. Achieving the goal of optimal nutrition and health for all requires efforts of the food system, from biotechnology and production, to processing, distribution, and marketing.